Analyzing the Impact of Brand Equity and Marketing Mix towards Consumer Loyalty: Case Study of Aqua in Surabaya - Christian Adi Basuki (iBuss Management, 2015)
This research is being done to know the impact of brand equity and marketing mix towards consumer loyalty of Aqua in Surabaya. The  data  was  gathered  using  simple  random  sampling by  distributing  o n l i n e  questionnaires  to  130  respondents  in  Surabaya.  The  data was  analyzed using Multiple Linear Regression Analysis. The  result  shows  that  the brand equity and marketing mix  simultaneously  have  significant  impact  on  consumer loyalty of Aqua in Surabaya. Meanwhile,  as  individual  dimension,  brand loyalty, brand awareness, perceived quality, price, and promotion have significant impact toward consumer loyalty of Aqua in Surabaya.Keywords: marketing, consumer behavior, brand equity, marketing mix, consumer loyalty